2020
DOI: 10.2478/fon-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mediation effects of health locus of control and hope on the relationship between stroke patients’ social support and self-management

Abstract: ObjectiveThis study aimed to identify the mediation effects of health locus of control (HLC) and hope between stroke patients’ social support and self-management.MethodsA cross-sectional study was conducted. A total of 300 Chinese stroke patients were recruited by convenient sampling from the acupuncture department of two Chinese Traditional Medical Hospitals in Tianjin Province from June to September 2018. The self-report questionnaires include Social Support Assessment Scale, Herth Hope Index, Mental Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(53 reference statements)
0
1
0
1
Order By: Relevance
“…More importantly, hope plays a partial mediating role between social support and self-management. Lei et al (2020) demonstrated that hope plays a mediating role in social support and self-management in stroke patients. Bao et al (2019) reported that hope can function as a mediator between social support and depressive symptoms among patients with central nervous system tumors.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, hope plays a partial mediating role between social support and self-management. Lei et al (2020) demonstrated that hope plays a mediating role in social support and self-management in stroke patients. Bao et al (2019) reported that hope can function as a mediator between social support and depressive symptoms among patients with central nervous system tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Výsledky ukázali pozitívny vzťah medzi interným presvedčením a self managementom po prekonaní CMP a negatívny vzťah medzi externým presvedčením a self-managementom po prekonaní CMP. Interné presvedčenie tiež pozitívne mediovalo vzťah medzi sociálnou oporou a self-managementom po prekonaní CMP (Lei, 2020).…”
Section: Umiestnenie Kontroly a Rekonvalescencia Po Prekonaní Cmpunclassified